Early onset neonatal meningitis in Australia and New Zealand, 1992–2002. Issue 4 (5th May 2005) - May, M; Daley, A J; Donath, S; Isaacs, D
Abstract : Objectives: To study the epidemiology of early onset neonatal bacterial meningitis (EONBM) in Australasia. Design: Prospective surveillance study, 1992–2002, in 20 neonatal units in Australia and New Zealand. EONBM was defined as meningitis occurring within 48 hours of delivery. Results: There were 852 babies with early onset sepsis, of whom 78 (9.2%) had EONBM. The incidence of early onset group B streptococcal meningitis fell significantly from a peak of 0.24/1000 live births in 1993 to 0.03/1000 in 2002 (p trend = 0.002). There was no significant change over time in the incidence of Escherichia coli meningitis. The rate of EONBM in very low birthweight babies was 1.09/1000 compared with the rate in all infants of 0.11/1000. The overall rate of EONBM was 0.41/1000 in 1992 and 0.06 in 2001, but this trend was not significant (p trend = 0.07). Case-fatality rates for EONBM did not change significantly with time. Birth weight <1500 g (odds ratio (OR) 7.2 (95% confidence interval (CI) 4.8 to 10.9)) and Gram negative bacillary meningitis (OR 3.3 (95% CI 2.2 to 4.9)) were significant risk factors for mortality. Sixty two percent of the 129 babies who died from early onset sepsis or suspected sepsis did not have a lumbar puncture performed. Conclusion: The incidence of early onset group B streptococcal meningitis has fallen, probably because of maternal intrapartum antibiotic prophylaxis, without a corresponding change in E coli meningitis. Gram negative bacillary meningitis still carries a worse prognosis than meningitis with a Gram positive organism.